All-hazards dataset mined from the US National Incident Management System 1999–2020 - St. Denis, Lise A.; Short, Karen C.; McConnell, Kathryn; Cook, Maxwell C.; Mietkiewicz, Nathan P.; Buckland, Mollie; Balch, Jennifer K. (Scientific data, 2023)
This paper describes a dataset mined from the public archive (1999–2020) of the US National Incident Management System Incident Status Summary (ICS-209) forms (a total of 187,160 reports for 35,170 incidents, including 34,478 wildland fires). This system captures detailed daily/regular information on incident development and response, including social and economic impacts. Most (98.4%) reports are wildland fire-related, with other incident types including hurricane, hazardous materials, flood, tornado, search and rescue, civil unrest, and winter storms. The archive, although publicly available, has been difficult to use for research due to multiple record formats, inconsistent data entry, and no clean pathway from individual reports to high-level incident analysis. Here, we describe the open-source, reproducible methods used to produce a science-grade version of the data, including formal connections made to other published wildland fire data products. Among other applications, this integrated and spatially augmented dataset enables exploration of the daily progression of the most costly, damaging, and deadly environmental-hazard events in recent US history. Measurement(s) wildfire Technology Type(s) NIMS/ICS Reporting Sample Characteristic - Environment wildfire Sample Characteristic - Location United States